2021
DOI: 10.1590/2177-6709.26.1.e2119150.oar
|View full text |Cite
|
Sign up to set email alerts
|

Influence of radiant exposure values from two third generation LED curing units on polymerization profile and microhardness of orthodontic composite under ceramic and metallic brackets

Abstract: Introduction: Third generation of LED light curing units might be used in short exposure periods for orthodontic brackets bonding. Objective: This study evaluated the effect of the different radiant exposure (RE) values: Manufacturers’ instructions (MI), ½ MI, 1/4 MI and Turbo mode. Two third-generation LED curing units were used: VALO® and Bluephase 20i® . The degree of conversion (DC) and Vickers hardness (VHN) of an orthodontic composite (OC) (Transbond XT) under metallic (MB) or ceramic brackets (CB) wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Other studies have compared differences in the DC values between metal and ceramic brackets. Reported DC values in the presence of metal brackets were found to be between 48% and 56%, which is lower when compared to ceramic brackets (ranging from 58% to 79%) [2,6,16,18], irrespective of the adhesive system used and the curing time. Shinya et al demonstrated that the presence of metal brackets reduced DC values by 17% to 29% compared to the control group (without brackets) for two commercially available orthodontic adhesive systems [8].…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…Other studies have compared differences in the DC values between metal and ceramic brackets. Reported DC values in the presence of metal brackets were found to be between 48% and 56%, which is lower when compared to ceramic brackets (ranging from 58% to 79%) [2,6,16,18], irrespective of the adhesive system used and the curing time. Shinya et al demonstrated that the presence of metal brackets reduced DC values by 17% to 29% compared to the control group (without brackets) for two commercially available orthodontic adhesive systems [8].…”
Section: Introductionmentioning
confidence: 82%
“…Most of the available studies on the DC of orthodontic adhesive systems have documented the values immediately after curing [2,6,[15][16][17][18][19], and studies of post-cure DC development are scarce [4]. In the study by Çörekçi et al, no significant difference was observed in DC values measured one day versus 30 days after curing for the tested materials [4].…”
Section: Introductionmentioning
confidence: 94%